Design Of Robot Motion Planning Algorithm For Wall Following Robot - Ali Hassan, Muhamad Khairul (Universiti Sains Malaysia, 2006)
This project demonstrates the use of Wall Following Algorithm for the development of mobile robot wall-following behaviors. Algorithms are developed for a simulated mobile robot that uses an array of range finders for navigation. Navigation algorithms are tested in a variety of differently shaped environments to encourage the development of robust solutions, and reduce the possibility of solutions based on memorization of a fixed set of movements. A typical wall-following robot evolutionary cycle is analyzed, and results are presented. Wall Following Algorithm is shown to be capable of producing robust wall-following navigation algorithms that perform well in each of the test environments used. In this project, i need to control the Robot to follow the wall. The robot is controlled by a BASIC Stamp microcontroller. The microcontroller is used to sequence the movement of the robot body sections via servos. The microcontroller also monitors the infrared sensor so that the ROBOT will avoid obstacles and wall as it explores. It can be automatically or manually control led through the internet/LAN. A user friendly GUI is developed using VISUAL BASIC to interface the user commands with the Robot controller. Computer A will be sent the data to computer B through the internet/LAN using JAVA program. Computer B will send the data to the BASIC Stamp and the BASIC Stamp will check their program. Then, the ROBOT will move depend on the program. The data will be sent to the ROBOT through the parallel port.